Biological Pathways Associated With the Development of Pulmonary Toxicities in Mesothelioma Patients Treated With Radical Hemithoracic Radiation Therapy: A Preliminary Study - Crovella, Sergio; Revelant, Alberto; Muraro, Elena; Moura, Ronald Rodrigues; Brandão, Lucas; Trovò, Marco; Steffan, Agostino; Zacchi, Paola; Zabucchi, Giuliano; Minatel, Emilio; Borelli, Violetta (Frontiers in Oncology, 2021)
Radical Hemithoracic Radiotherapy (RHR), after lung-sparing surgery, has recently become a concrete therapeutic option for malignant pleural mesothelioma (MPM), an asbestos-related, highly aggressive tumor with increasing incidence and poor prognosis. Although the toxicity associated to this treatment has been reduced, it is still not negligible and must be considered when treating patients. Genetic factors appear to play a role determining radiotherapy toxicity. The aim of this study is the identification of biological pathways, retrieved through Whole Exome Sequencing (WES), possibly associated to the development of lung adverse effects in MPM patients treated with RHR. The study included individuals with MPM, treated with lung-sparing surgery and chemotherapy, followed by RHR with curative intent, and followed up prospectively for development of pulmonary toxicity. Due to the strong impact of grade 3 pulmonary toxicities on the quality of life, compared to less serious adverse events, for genetic analyses patients were divided into a none or tolerable pulmonary toxicity (NoSTox) group (Grade ≤2) and a severe pulmonary toxicity (STox) group (Grade=3). Variant Enrichment Analysis allowed us to identify different pathway signatures characterizing NoSTox and Stox patients, allowing to formulate hypotheses on the protection from sides effects derived from radiotherapy as well as factors predisposing to a worst response to the treatment. Our findings, being aware of the small number of patients analyzed, could be considered as a starting point for the definition of a panel of pathways, possibly helpful in the management of MPM patients.